Theoretical Design of a Belt Sander Wood Sanding Machine for Small-Scale Industries - Candra Prayoga Aditama Paputungan; Herotje Siwi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Manual wood sanding in small workshops requires considerable time and labor but may produce inconsistent surface quality. This study aimed to develop a theoretical design for a belt-sander wood sanding machine and determine the specifications of its main components. An engineering design approach was used, comprising a literature review, identification of design requirements, component selection, preparation of two- and three-dimensional AutoCAD drawings, and analytical calculations for the motor, pulley and V-belt transmission, rollers, shaft, and frame. The proposed machine uses a 1 HP (0.746 kW), 1390 rpm electric motor, 80 mm driving and 120 mm driven pulleys, an A-type V-belt, 100 mm rollers, a 25 mm S45C shaft, UCP205 bearings, and a 40 × 40 × 2 mm hollow-steel frame. The calculations yielded a drive-roller speed of 926.67 rpm, motor torque of 5.13 N·m, theoretical roller torque of 7.70 N·m, sanding-belt speed of 4.85 m/s, tangential force of 154 N, theoretical V-belt length of 1115 mm, roller mass of approximately 5.55 kg, and shaft torsional shear stress of 2.51 N/mm². These results provide a technical basis for prototype development; however, operational feasibility remains unconfirmed because combined loading, vibration, surface roughness, productivity, and actual power consumption have not been experimentally evaluated.